2012
DOI: 10.1371/journal.pone.0052371
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Subordinate Colony Housing (CSC) as a Model of Chronic Psychosocial Stress in Male Rats

Abstract: Chronic subordinate colony housing (CSC) is an adequate and reliable mouse model of chronic psychosocial stress, resulting in reduced body weight gain, reduced thymus and increased adrenal weight, long-lasting anxiety-like behaviour, and spontaneous colitis. Furthermore, CSC mice show increased corticotrophin (ACTH) responsiveness to acute heterotypic stressors, suggesting a general mechanism which allows a chronically-stressed organism to adequately respond to a novel threat. Therefore, the aim of the present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 64 publications
5
23
0
1
Order By: Relevance
“…In agreement with previous reports, we showed that CSC mice exhibited reduced body weight gain which is a wellestablished physiological marker of chronic stress in both mice (Reber et al 2007;Reber and Neumann 2008;Singewald et al 2009) and rats (Berton et al 1998;Nyuyki et al 2012;Plaznik et al 1993;Stefanski et al 2001). A reduction in body weight gain was also observed in acutely defeated animals (Berton et al 1998).…”
Section: Consequences Of Csc On Body Weight Gain and Anxiety-like Behsupporting
confidence: 92%
“…In agreement with previous reports, we showed that CSC mice exhibited reduced body weight gain which is a wellestablished physiological marker of chronic stress in both mice (Reber et al 2007;Reber and Neumann 2008;Singewald et al 2009) and rats (Berton et al 1998;Nyuyki et al 2012;Plaznik et al 1993;Stefanski et al 2001). A reduction in body weight gain was also observed in acutely defeated animals (Berton et al 1998).…”
Section: Consequences Of Csc On Body Weight Gain and Anxiety-like Behsupporting
confidence: 92%
“…However, since the decreased home-cage activity in the SDL group was restored to control levels on days 14 and 20, and, given that no differences in body weight gain were found between the SDL and SHC groups, our results are overall in accordance with our previous study showing that repeated SDD (night stress) has more profound effects than repeated SDL (day stress). In addition, we observed a reduced weight of thymus from SDD, but not SDL, mice that is a reliable indicator of chronic stress (Nyuyki et al, 2012). Taken together, we consider the SD paradigm valid also in the PER2::LUC mice.…”
Section: Validation Of the Stress Model In Per2::luc Micesupporting
confidence: 60%
“…Unlike the spleen, the thymus often shrinks during stress and that shrinkage is directly proportional to the degree of stress and increase in plasma adrenocorticotropic hormone and corticosterone levels [33]. TNBS treatment resulted in significant decrease of thymus weight on days 3 and 6 (Fig.…”
Section: Resultsmentioning
confidence: 99%